Who is Responsible for Responsible Innovation? Lessons From an Investigation into Responsible Innovation in Health; Comment on "What Health System Challenges Should Responsible Innovation in Health Address? Insights From an International Scoping Review" - Bernd Carsten Stahl (Kerman University of Medical Sciences, 2019)
Responsible innovation in health (RIH) takes the ideas of responsible research and innovation (RRI) and applies them to the health sector. This comment takes its point of departure from Lehoux et al which describes a structured literature review to determine the system-level challenges that health systems in countries at different levels of human development face. This approach offers interesting insights from the perspective of RRI, but it also raises the question whether and how RRI can be steered and achieved across healthcare systems. This includes the question who, if anybody, is responsible for responsible innovation and which insights can be drawn from the systemic nature RIH.